2016
DOI: 10.1038/ajg.2016.343
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors Do Not Increase Risk for Clostridium difficile Infection in the Intensive Care Unit

Abstract: Objectives Patients in the intensive care unit (ICU) frequently receive proton pump inhibitors (PPIs) and have high rates of Clostridium difficile infection (CDI). PPIs have been associated with CDI in hospitalized patients, but ICU patients differ fundamentally from non-ICU patients and few studies have focused on PPI use exclusively in the critical care setting. We performed a retrospective cohort study to determine the associations between PPIs and healthcare facility–onset CDI in the ICU. Methods We anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 56 publications
3
27
1
2
Order By: Relevance
“…Along with previous studies, these data suggest that PPIs do not meaningfully alter clinical outcomes with respect to some of the most important ICU infections: bloodstream infections, VAP, or Clostridium difficile infection. 35 In the ICU setting, any effects of PPIs may simply be too subtle or too short-lived to exert a downstream effect on risk for BSI or other infections.…”
Section: Discussionmentioning
confidence: 99%
“…Along with previous studies, these data suggest that PPIs do not meaningfully alter clinical outcomes with respect to some of the most important ICU infections: bloodstream infections, VAP, or Clostridium difficile infection. 35 In the ICU setting, any effects of PPIs may simply be too subtle or too short-lived to exert a downstream effect on risk for BSI or other infections.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that PPIs alter the colonic flora by facilitating the growth of potentially pathogenic organisms in the gastrointestinal tract . A few studies reported no increased risk of developing CDI if patients are exposed to a PPI . However, significantly more clinical studies found the use of a PPI among hospitalized patients as a risk factor for the development of CDI …”
Section: Discussionmentioning
confidence: 99%
“…While most studies suggest a higher risk for CDI during PPI treatment, there are contradictory reports in literature [19]. Given that acid suppression drugs may be over-prescribed in surgical settings, consideration should be given to stopping PPIs in patients at high risk of CDI [8].…”
Section: Discussionmentioning
confidence: 99%
“…The prophylactic dose given immediately before surgery is associated with dramatically reduced rates of wound infection and post-operative sepsis [18]. It is likely that any slightly increased risk of post-operative CDI associated with such prophylactic use of antibiotics would be outweighed by benefit [8].While most studies suggest a higher risk for CDI during PPI treatment, there are contradictory reports in literature [19]. Given that acid suppression drugs may be over-prescribed in surgical settings, consideration should be given to stopping PPIs in patients at high risk of CDI [8].…”
mentioning
confidence: 99%